2019
DOI: 10.1002/smll.201902577
|View full text |Cite
|
Sign up to set email alerts
|

Nanoagents Based on Poly(ethylene glycol)‐b‐Poly(l‐thyroxine) Block Copolypeptide for Enhanced Dual‐Modality Imaging and Targeted Tumor Radiotherapy

Abstract: Future healthcare requires development of novel theranostic agents that are capable of not only enhancing diagnosis and monitoring therapeutic responses but also augmenting therapeutic outcomes. Here, a versatile and stable nanoagent is reported based on poly(ethylene glycol)‐b‐poly(l‐thyroxine) (PEG‐PThy) block copolypeptide for enhanced single photon emission computed tomography/computed tomography (SPECT/CT) dual‐modality imaging and targeted tumor radiotherapy in vivo. PEG‐PThy acquired by polymerization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Deng and co-workers reported a block copolypeptide for SPECT/CT dual-modality imaging. [131] Different from the common strategy to only load radionuclides for SPECT, they modified polypeptide with both iodinated molecules for enhanced CT and 125 I for SPECT. They utilized iodineexchange reaction to easily label 125 I on the iodinated side chain of polypeptide.…”
Section: Peptide/polypeptide-based Materials For Spect and Spect/ctmentioning
confidence: 99%
See 1 more Smart Citation
“…Deng and co-workers reported a block copolypeptide for SPECT/CT dual-modality imaging. [131] Different from the common strategy to only load radionuclides for SPECT, they modified polypeptide with both iodinated molecules for enhanced CT and 125 I for SPECT. They utilized iodineexchange reaction to easily label 125 I on the iodinated side chain of polypeptide.…”
Section: Peptide/polypeptide-based Materials For Spect and Spect/ctmentioning
confidence: 99%
“…Also, H&E staining results showed negligible damage on major organs including spleen and liver, which indicated the excellent biocompatibility of this polypeptide-based platform. Furthermore, 131 I could also be introduced into this polypeptide platform with iodine-exchange reaction, indicating the potential to combine enhanced imaging and radiotherapy.…”
Section: Peptide/polypeptide-based Materials For Spect and Spect/ctmentioning
confidence: 99%
“…showed efficient uptake and superb antiproliferative activity in B16F10 melanoma and HCT-116 tumor cells, respectively, leading to significantly more effective inhibition of both tumor models than nontargeted controls. , cRGD-decorated lipopepsomes (cRGD-LPP) revealed high loading and targeted delivery of DOX·HCl to an orthotopic A549 human lung tumor in nude mice, resulting in a significantly improved survival rate as compared to nontargeted counterpart and clinically used liposomal DOX (Lipo-DOX) . Robust and versatile nanoagents developed from PEG- b -poly­( l -thyroxine) following cRGD functionalization have exhibited enhanced single photon emission computed tomography/computed tomography (SPECT/CT) dual-modality imaging and targeted radiotherapy in subcutaneous B16F10 melanoma and orthotopic A549 lung tumor . Of note, selective cell penetrating CPP33 peptide-functionalized chimaeric lipopepsomes were developed from PEG–PAPA-PLys for selective delivery of siPLK1 to A549 human lung cancer cells in vivo, inducing effective tumor suppression and prolonged survival time .…”
Section: Active Tumor-targeting Nanomedicines Based On Synthetic Poly...mentioning
confidence: 99%
“…72 Robust and versatile nanoagents developed from PEG-b-poly(L-thyroxine) following cRGD functionalization have exhibited enhanced single photon emission computed tomography/computed tomography (SPECT/CT) dual-modality imaging and targeted radiotherapy in subcutaneous B16F10 melanoma and orthotopic A549 lung tumor. 73 Of note, selective cell penetrating CPP33 peptide-functionalized chimaeric lipopepsomes were developed from PEG− PAPA-PLys for selective delivery of siPLK1 to A549 human lung cancer cells in vivo, inducing effective tumor suppression and prolonged survival time. 74 In a recent study, antihuman tissue factor antibody fragment (Fab′)-installed PIC micelles were constructed from PEG−PLys and siRNA, and the results showed that three molecules of Fab′-installed PIC micelles had the highest binding affinity and the most efficient gene silencing activity in pancreatic cancer BxPC3 cells compared with one or two molecule(s) of Fab′-installed PIC micelles, and exhibited high penetrability in BxPC3 spheroids.…”
Section: Active Tumor-targeting Nanomedicines Based On Synthetic Poly...mentioning
confidence: 99%
“…As references have reported, the combined application of PDT or PTT with other therapeutic tools can effectively overcome the above mentioned issues with reduced dosage and improved therapy efficacy 9,19–22 . For example, the Liu group reported a facile and low‐cost approach to designing a di‐functional nanoplatform (CuS@mSiO 2 ‐PEG) as a NIR light responsive drug delivery system for efficient chemo‐photothermal therapy 9 .…”
Section: Introductionmentioning
confidence: 99%